Euro Adoption – the Illusion of the Monetary Integration of Romania - Cristina Duhnea; Silvia Ghita-Mitrescu; Diane Paula Corina Vancea (CES Working Papers, 2012)
The accession to the European Union for Central and Eastern Europe countries involved their requirement to start the process of the European Monetary Union integration. The desire to enjoy the benefits of EU membership has made both the 10 countries that joined EU in 2004 and Romania and Bulgaria which became EU member in 2007 to engage on the path to join the European single currency endeavoring to meet not only the nominal convergence criteria but also real convergence. This paper makes an analysis of the Romania's capacity to achieve the nominal convergence criteria in the current context. The change of the financial and economic conditions due to the crisis that spread worldwide during 2007 - 2008 changed the issue from "Romania can fulfill the nominal convergence criteria?” in "Is it advisable for Romania to adopt the Euro, given the uncertainty clouds over the currency's future?” The analysis is made by considering the comparative situation of other countries that are in the process of joining the single currency. The objective of the research undertaken in this paper is to investigate Romania's capacity to approach the nominal convergence criteria and so realistic goal of joining the Euro it is.
Keywords: E43; G01; F36; 330; Euro; European Monetary Union; Romania; nominal convergence; convergence criteria; Euro adoption Romania